Soziale und ethnische Konflikte im Restrukturierungsprozess: Die Unruhen vom Frühjahr 1992 in Los Angeles - Thieme, Günter; Laux, Hans Dieter (ERDKUNDE, 1995)
The riots which occurred in Los Angeles in spring 1992 must be considered as the severest case of civil unrest in recent American history. After four police officers charged with brutally beating a black motorist had been acquitted, large parts of the city went up in flames. The riots had a distinctly multi-ethnic character far beyond any simplistic interpretation as a confrontation between Afro-Americans and whites. Whereas most of the victims were Korean shop owners, the rioters equally included Hispanics and Afro Americans. This paper seeks to reveal the causes of this severe civil unrest. After a discussion of the controversial arguments of conservative, radical and liberal authors concerning the roots and preconditions of the riots the role of the major ethnic groups in the restructured labor market of Los Angeles is analyzed in detail. Especially the black population turned out to be the losers in the process of economic restructuring, whereas the recent Latino immigrants filled many jobs in the low paid manufacturing and service sectors of the increasingly polarized labor market. In contrast, many Asian immigrants achieved considerable socio-economic success by entering the upper segment of the labor market or by turning to self-employment. Although the riots can only be understood in this general context of restructuring their outbreak was caused by the specific local conflicts, socio-economic disparities and living conditions in South Central Los Angeles. In this persistently neglected part of the city the clash of young, partly undocumented immigrant populations from Latin America with the incumbent black residents stricken with unemployment, poverty and broken families, and absentee Korean shop owners (middleman minority) had created an explosive potential of conflict and hostility. Three years after the riots there is little hope that the severe problems of South Central Los Angeles, as of many other central cities in the USA, will be solved in the foreseeable future.